Ileoanal Pouch Syndrome Is Common and Associated With Significant Disability in Patients With Ulcerative Colitis Undergoing IPAA. Issue 12 (22nd September 2022) - Li, Song; Ding, Chao; Zhu, Feng; Wang, Zhongyuan; Yu, Zeqian; Tan, Dong; Zhang, Tenghui; Gong, Jianfeng
Abstract : BACKGROUND: Recently, ileoanal pouch syndrome (IPS) has been proposed and defined according to a series of patient-centered bowel symptoms and consequences after ileoanal pouch surgery. OBJECTIVE: The purpose of this study was to investigate the prevalence of IPS and the related disability in UC patients undergoing IPAA. DESIGN: This was a cross-sectional study. SETTING: This study was conducted in a tertiary center. PATIENTS: Data of 128 UC-related IPAA from October 2014 to May 2021 were collected. MAIN OUTCOME MEASURES: Primary outcomes were prevalence of IPS. RESULTS: One hundred twenty-eight patients were enrolled with a median postoperative follow-up of 2.64 (IQR, 1.31–3.80) years. The prevalence of IPS and its constituent symptoms and consequences are lower for patients with longer follow-up after ileostomy reversal. Fecal incontinence and pad usage had the greatest impact on the quality of life affecting 29% and 31% of patients. IPS group had a significantly higher IBD-Disability Index score compared to the non-IPS group (27.25 vs 12.15, p < 0.001). Multivariate analysis showed that 4 symptoms (fecal incontinence, clustering, fragmentation and incomplete evacuation, and nocturnal symptoms) and 2 consequences (pad usage and negative mental alterations) were associated with increased IBD-Disability Index ( p < 0.05). For patients followed-up for >2 years, multivariate analysis showed that male gender (OR, 4.485; 95% CI, 1.354–14.857; p = 0.014), preoperative duration of disease (OR, 1.013; 95% CI, 1.001–1.025; p = 0.031), and postoperative follow-up (OR, 0.462; 95% CI, 0.244–0.876; p = 0.049) were independently associated with IPS. LIMITATIONS: This is a single-center cross-sectional study rather than a prospective multicenter large longitudinal study. CONCLUSIONS: IPS is a common situation negatively affecting the quality of life for patients with ulcerative colitis undergoing IPAA, and its rate decreased over time from ileal pouch surgery. See Video Abstract at http://links.lww.com/DCR/C41 . EL SÍNDROME DEL RESERVORIO ILEOANAL ES COMÚN Y ESTÁ ASOCIADO CON UNA DISCAPACIDAD SIGNIFICATIVA EN PACIENTES CON CU CON RESERVORIO ILEAL Y ANASTOMOSIS RESERVORIO-ANAL: ANTECEDENTES: Recientemente se propuso y definió el síndrome del reservorio ileoanal de acuerdo con una serie de síntomas intestinales centrados en el paciente y las consecuencias después de la cirugía del reservorio ileoanal. OBJETIVO: El propósito de este estudio fue investigar la prevalencia del síndrome del reservorio ileoanal y la discapacidad relacionada en pacientes con colitis ulcerosa con reservorio ileal y anastomosis reservorio-anal. DISEÑO: Este fue un estudio transversal. ESCENARIO: Este estudio se realizó en un centro terciario. PACIENTES: Se recopilaron datos de 128 pacientes con reservorio ileal por colitis ulcerosa desde octubre de 2014 hasta mayo de 2021. PRINCIPALES MEDIDAS DE RESULTADO: Los resultados primarios fueron la prevalencia del síndrome del reservorio ileoanal. RESULTADOS: Ciento veintiocho pacientes fueron reclutados con una mediana de seguimiento postoperatorio de 2, 64 (IQR, 1, 31-3, 80) años. La prevalencia del síndrome del reservorio ileoanal y sus síntomas y consecuencias constituyentes es menor para los pacientes con un seguimiento más prolongado después de la reversión de la ileostomía. La incontinencia fecal y el uso de compresas tuvieron el mayor impacto en la calidad de vida, afectando al 29% y al 31% de los pacientes. El grupo con síndrome del reservorio ileoanal tuvo una puntuación del índice de discapacidad por enfermedad inflamatoria intestinal significativamente más alta en comparación con el grupo sin síndrome del reservorio ileoanal (27, 25 frente a 12, 15, p <0, 001). El análisis multivariado mostró que 4 síntomas (incontinencia fecal, agrupamiento, fragmentación y evacuación incompleta y síntomas nocturnos) y 2 consecuencias (uso de toallas higiénicas y alteraciones mentales negativas) se asociaron con un aumento del índice de discapacidad por enfermedad inflamatoria intestinal (p <0, 05). Para los pacientes seguidos durante más de dos años, el análisis multivariado mostró que el sexo masculino (OR, 4, 485; IC 95%, 1, 354-14, 857; p = 0, 014), la duración preoperatoria de la enfermedad (OR, 1, 013; IC 95%, 1, 001-1, 025; p = 0, 031) y el seguimiento postoperatorio (OR, 0, 462; IC 95%, 0, 244-0, 876; p = 0, 049) se asociaron de forma independiente con el síndrome del reservorio ileoanal. LIMITACIONES: Este es un estudio transversal de un solo centro en lugar de un gran estudio longitudinal prospectivo multicéntrico. CONCLUSIONES: El síndrome del reservorio ileoanal es una situación común que afecta negativamente la calidad de vida de los pacientes con colitis ulcerosa sometidos a anastomosis del reservorio ileal-anal, y su tasa disminuyó con el tiempo a partir de la cirugía del reservorio ileal. El sexo masculino y la mayor duración preoperatoria de la enfermedad son factores de riesgo importantes para el síndrome del reservorio ileoanal. Consulte Video Resumen en http://links.lww.com/DCR/C41 . (Traducción—Dr. Felipe Bellolio )